2022
DOI: 10.3390/toxins14090632
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Biological Activities and Structural Modifications of Dehydroabietic Acid

Abstract: Dehydroabietic acid is a tricyclic diterpenoid resin acid isolated from rosin. Dehydroabietic acid and its derivatives showed lots of medical and agricultural bioactivities, such as anticancer, antibacterial, antiviral, antiulcer, insecticidal, and herbicidal activities. This review summarized the research advances on the structural modification and total synthesis of dehydroabietic acid and its derivatives from 2015 to 2021, and analyzed the biotransformation and structure-activity relationships in order to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…Dehydroabietic Acid (DA) is a tricyclic diterpenoid derivative found in conifers (Hao et al, 2022), and has been demonstrated to reverse hepatic iron sagging induced by HFD‐induced NAFLD in mice by elevating the expression of the iron apoptosis blocker FSP1 protein. Moreover, DA treatment reduced ROS production by more than 50% after upregulating the expression of HO‐1, GPX4, GSS, GCL, and UGT; these genes are related to oxidative stress pathways downstream of Nrf2.…”
Section: The Use Of Natural Products In the Treatment Of Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…Dehydroabietic Acid (DA) is a tricyclic diterpenoid derivative found in conifers (Hao et al, 2022), and has been demonstrated to reverse hepatic iron sagging induced by HFD‐induced NAFLD in mice by elevating the expression of the iron apoptosis blocker FSP1 protein. Moreover, DA treatment reduced ROS production by more than 50% after upregulating the expression of HO‐1, GPX4, GSS, GCL, and UGT; these genes are related to oxidative stress pathways downstream of Nrf2.…”
Section: The Use Of Natural Products In the Treatment Of Nafldmentioning
confidence: 99%
“…It was also observed that this NOX4/NLRP3 pathway reduces harmful bacterial abundance while increasing beneficial bacterial abundance as well as improving intestinal structure to achieve the course of NAFLD disease (Nie et al, 2021). Dehydroabietic Acid (DA) is a tricyclic diterpenoid derivative found in conifers (Hao et al, 2022), and has been demonstrated to reverse hepatic iron sagging induced by HFD-induced NAFLD in mice by elevating the expression of the iron apoptosis blocker FSP1 protein. Moreover, DA treatment reduced ROS production by more than 50% after upregulating the expression of HO-1, GPX4, GSS, GCL, and UGT; these genes are related to oxidative stress pathways downstream of Nrf2.…”
Section: Therapeutic Effects Of Terpene Components On Nafldmentioning
confidence: 99%
“…DHA and its derivatives show a variety of biological activities, including antiviral, antifungal, antibacterial, anti-aging, anti-inflammatory, and BK channel-opening activities. 6–13 In particular, a number of DHA derivatives have been reported in recent years, which show significant antitumour properties via DNA binding, the induction of apoptosis (1,2,3-triazole dehydroabietic acid hybrids, a ), and PI3K (1 H -benzo[ d ]imidazole derivatives of dehydroabietic acid, b ) or MEK inhibition mechanisms. 14–16 According to these results, we became interested in exploring novel and more effective anticancer agents from DHA.…”
Section: Introductionmentioning
confidence: 99%
“…Cantharidin and (S)-(-)-palasonin showed different toxicity to P. xylostella, with median lethal concentrations, and quinolizidine alkaloids and neem-based products exhibited moderate acaricidal activities against T. urticae [9][10][11]. Therefore, the research and development of potential pesticide alternatives from bioactive plant natural products has received much attention in recent years [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%